Chronic Ocular Hypertensive Rat Model using Microbead Injection: Comparison of Polyurethane, Polymethylmethacrylate, Silica and Polystyene Microbeads. (September 2014) - Rho, Seungsoo; Park, Insung; Seong, Gong Je; Lee, Naeun; Lee, Chang-Kyu; Hong, Samin; Kim, Chan Yun
Abstract Purpose: To establish and assess an ocular hypertensive rat model using intracameral injection with various microbeads of different sizes and materials. Methods: Chronic elevation of intraocular pressure (IOP) was induced by the injection of various microbeads into the anterior chamber of Sprague-Dawley rat eyes. We compared the IOPs induced by the injection of different microbeads [7- and 17-µm polyurethane (PU), 7- and 15-µm polymethylmethacrylate (PMMA), 13-µm silica, and 15-µm polystyrene (PS)] and selected the appropriate microbeads for a chronic ocular hypertensive model in terms of IOP elevation and adverse events. IOP changes were observed for 4 weeks after microbead injections. Axonal degeneration was assessed with transmission electron microscopic photographs and RGC loss was assessed with retrograde labeling. Results: Seventy-eight rats were included. Three days after a single injection of microbeads, IOPs were increased by 24.0% by 7-µm PU microbeads, 101.8% by 17-µm PU microbeads, 56.6% by 7-µm PMMA microbeads, 22.0% by 15-µm PMMA microbeads, 153.0% by 13-µm silica microbeads, and 34.7% by 15-µm PS microbeads. 17-µm PU microbeads produced constant IOP elevation with good reproducibility (standard deviation of <6.5 mmHg). Silica injected eyes showed severe inflammation. Sustained IOP elevation by two injections of 17-µm PU microbeads resulted in a 42% axon loss and 36.5% RGC loss (p < 0.05, Mann–Whitney U test). Conclusions: PU microbead injections offer an applicable and versatile model for a chronic ocular hypertensive model in rats. Among several biomaterials, PU microbeads produced a more stable IOP elevation without adverse events.